2006
DOI: 10.1055/s-2006-925448
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment versus endoscopic sphincterotomy in the initial management of acute cholecystitis in elderly patients at high surgical risk

Abstract: The clinical course after endoscopic sphincterotomy improved in the majority of elderly patients suffering from acute cholecystitis, suggesting that early relief of obstruction at the level of the common channel reduces the risk of developing biliary sepsis. The majority of these patients can undergo surgery electively or can receive further conservative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 5 publications
4
30
0
4
Order By: Relevance
“…Since the source of infection is not controlled using this approach though, many patients might still develop biliary sepsis. A prospective study of 53 elderly patients with acute cholecystitis treated conservatively showed that 16 patients (30%) suffered from biliary sepsis requiring emergency surgery, one of whom died [35] . A prospective study of 42 elderly patients with acute cholecystitis and an APACHE-II score ≥ 12 showed that 7 patients (17%) suffered from ongoing sepsis, all of whom died [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Since the source of infection is not controlled using this approach though, many patients might still develop biliary sepsis. A prospective study of 53 elderly patients with acute cholecystitis treated conservatively showed that 16 patients (30%) suffered from biliary sepsis requiring emergency surgery, one of whom died [35] . A prospective study of 42 elderly patients with acute cholecystitis and an APACHE-II score ≥ 12 showed that 7 patients (17%) suffered from ongoing sepsis, all of whom died [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Se ha reportado que la vimentina es un marcador de células proliferativas en los conductos pancreáticos 16 , sin embargo otros estudios reportaron inmunorreactividad negativa para vimentina en células de los conductos pancreáticos 9 , este hecho se confirma en nuestros casos, en los que ninguna estructura tubular pancreática fue reactiva a vimentina. Las estructuras tubulares y epiteliales fueron inmunorreactivas a citokeratinas 7,8,18,19,20 y a CA19-9; las estructuras epiteliales fueron reactivas a villina y CEA. La actividad exocrina fue documentada mediante inmunorreactividad a α1-antitripsina y α1-quimotripsina.…”
Section: A S O S C L í N I C O Sunclassified
“…Se ha descrito que el reflujo de enzimas pancreáticas hacia la vía y vesícula biliar, puede llevar al desarrollo de síntomas biliares en pacientes sin cálculos con lesiones polipoideas 17 y a colecistitis aguda en pacientes con cálculos 18,19 . La amilasa eventualmente lesionaría la mucosa de la vía y vesícula biliar desarrollando hiperplasia y displasia de la mucosa 20-22 y eventualmente cáncer de vesícula biliar 23 .…”
Section: A S O S C L í N I C O Sunclassified
See 2 more Smart Citations